Irreversible Resistive State Switching in Devices with a Homoleptic Cobalt(II) Complex Active Layer. Issue 12 (10th May 2021) - Barman, Biswajit K.; Khatua, Manas; Goswami, Bappaditya; Samanta, Subhas; Vijayaraghavan, Ratheesh K.
Abstract: Molecules with bi‐stable electronic transport behaviour have been in upfront research topics of the molecular semiconductor devices in the past few decades due to the use of such materials in resistive data storage devices. Transition metal complexes (TMC) are expected to be potential candidates in regard to the tunable and manifold redox behaviour expecting multiple bulk transport states. Finding alternate mechanisms in such devices with TMC as the active layer materials would revoke the multifaceted approach to the functional gain. We have succeeded in demonstrating write once‐read many (WORM) type of resistive memory device using a homoleptic Cobalt(II) (Co(II)) complex with large on/off current ratio ensuring the easy readout process at lower voltage. The advantage of this device was the turn on voltage was found to be the low (<2.7 V) operational voltage and the success ratio of the devices were more than 83%. The durability of the stored data was found to be more than 35, 000 seconds which ensures the stability of the bistable state in the fabricated devices. Such ambient stable, solution processable devices are important for the large‐scale printable devices. The manuscript describes the preparation, optical and electrochemical characterisation of the metal complex used along with a detailed mechanistic investigations and electrical characterisation of memory device obtained from a stable cobalt complex. Abstract : Write once‐read many (WORM) type of resistive state switching in devices with a homoleptic cobalt(II) complex active layer is demonstrated. The data retention time for the memory device under ambient condition is found to be >35, 000 seconds which ensures the stability of the bistable state. The manuscript describes the mechanistic investigations and electrical characterisation of memory devices.